Analisis Proses Perawatan Auxiliary Power Units pada Pesawat Udara (Studi Kasus: Keterlambatan Pengembalian APU GTCP 131-9 di PT GAA Tbk) - Nur Fadilah Fatma; Henri Ponda; Bayu Munggara (Universitas Bunda Mulia, 2020)
PT. GAA is an international company that employs 4300 employees based in Tangerang, Banten, Indonesia. PT. GAA is able to maintain and repair aircraft, ranging from light repair maintenance to overhauls, maintenance and repair of engines, APU (Auxiliary Power Units) and aircraft components, and cabin modifications. The time to complete the repair of APU sometimes exceeds the Turnaround Time (TAT) that is determined which is 45 days. In fact, there are many delays that occur in returning APU to consumers. In this research report applying the Gantt chart, RCA and 5 Whys Analysis methods, to find out the main causes of delays in the repair process through 10 gates and to find out which gate has the longest delay. From the results of the study, it was found that after the 131-9 APU data collection amounted to 30 units, for 1 year, it was found that the gate which experienced the longest delay was Gate 5, Gate 3, Gate 8 and Gate. 7 and the main cause is the limited ability to repair the APU, the lack of personnel ready to work and the technical problems that occur during APU testing and limited assembly space, equipment for APU assembly and supplies.